Redundant and incoherent regulations of multiple phenotypes suggest microRNAs’ role in stability control - Liufu, Zhongqi; Zhao, Yixin; Guo, Li; Miao, Guangxia; Xiao, Juan; Lyu, Yang; Chen, Yuxin; Shi, Suhua; Tang, Tian; Wu, Chung-I (Genome Research, 2017)
Each microRNA (miRNA) represses a web of target genes and, through them, controls multiple phenotypes. The difficulties inherent in such controls cast doubt on how effective miRNAs are in driving phenotypic changes. A “simple regulation” model posits “one target–one phenotype” control under which most targeting is nonfunctional. In an alternative “coordinate regulation” model, multiple targets are assumed to control the same phenotypes coherently, and most targeting is functional. Both models have some empirical support but pose different conceptual challenges. Here, we concurrently analyze multiple targets and phenotypes associated with the miRNA-310 family (miR310s) of Drosophila. Phenotypic rescue in the mir310s knockout background is achieved by promoter-directed RNA interference that restores wild-type expression. For one phenotype (eggshell morphology), we observed redundant regulation, hence rejecting “simple regulation” in favor of the “coordinate regulation” model. For other phenotypes (egg-hatching and male fertility), however, one gene shows full rescue, but three other rescues aggravate the phenotype. Overall, phenotypic controls by miR310s do not support either model. Like a thermostat that controls both heating and cooling elements to regulate temperature, redundancy and incoherence in regulation generally suggest some capacity in stability control. Our results therefore support the published view that miRNAs play a role in the canalization of transcriptome and, hence, phenotypes.